(untitled) (Publicaciones en Ciencias y Tecnología, 2018)
The present edition of Publications in Sciences and Technology (PCyT) corresponds to Volume 12, No. 2, July-December 2018, dedicated to the dissemination of results of the Research Group’s Projects in Fuzzy Databases of the Simón Bolívar University (USB ), in the context of the tribute of this journal to Lofti Zadeh, father of the diffuse logic.